Separable Recursive Gradient Algorithm for Dynamical Systems Based on the Impulse Response Signals - Xu, Ling; Ding, Feng; Yang, Erfu (International journal of control, automation, and systems, 2020)
The identification for process control systems is considered in this paper based on the impulse response signals from the discrete measurements. By taking advantage of impulse signals and through the model parameter decomposition, two dependent identification models are constructed and two identification sub-algorithms are presented based on the nonlinear gradient optimization. In terms of the associated items of the parameters to be estimated between two derived sub-algorithms, a separable recursive gradient parameter estimation method is proposed by designing an interactive and recursive estimation. The performance tests and the comparison experiments are carried out by the simulation examples.